Super carotene carrot - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A new carrot containing three to five times the usual amount of vitamin A has been developed by the USDA Department of Horticulture. The new carrot, called Beta III, has 270ppm of carotene, and has been developed for use in developing countries to...